2019
DOI: 10.1056/nejmoa1810641
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Alertness in a Duty-Hour Flexibility Trial in Internal Medicine

Abstract: BACKGROUND A purpose of duty-hour regulations is to reduce sleep deprivation in medical trainees, but their effects on sleep, sleepiness, and alertness are largely unknown. METHODS We randomly assigned 63 internal-medicine residency programs in the United States to follow either standard 2011 duty-hour policies or flexible policies that maintained an 80-hour workweek without limits on shift length or mandatory time off between shifts. Sleep duration and morning sleepiness and alertness were compared between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 40 publications
(40 reference statements)
2
68
0
3
Order By: Relevance
“…Sleep deprivation (SD) is becoming increasingly common in our hectic society. 1 Understanding the consequences of SD and neuroimaging mechanisms is of great importance. 2 , 3 Previous task and resting-state functional magnetic resonance imaging (rs-fMRI) studies have verified extensive voxel-level and network-level brain-function alterations after SD, 4 , 5 largely covering the frontal lobe, thalamus, default-mode network and frontoparietal network.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep deprivation (SD) is becoming increasingly common in our hectic society. 1 Understanding the consequences of SD and neuroimaging mechanisms is of great importance. 2 , 3 Previous task and resting-state functional magnetic resonance imaging (rs-fMRI) studies have verified extensive voxel-level and network-level brain-function alterations after SD, 4 , 5 largely covering the frontal lobe, thalamus, default-mode network and frontoparietal network.…”
Section: Introductionmentioning
confidence: 99%
“…Recent changes have allowed for flexibility in the previously mandated standard duty hours that were implemented by the Accreditation Council for Graduate Medical Education (ACGME) in July 2011. The potential impact of relaxing duty hour restrictions was assessed in the Individualized Comparative Effectiveness of Models Optimizing Patient Safety and Resident Education (iCOMPARE) trial, which recently demonstrated that chronic sleep loss and sleepiness were similar among interns in flexible programs and standard programs 44 . Further, no detriment to patient safety outcomes was observed 45 .…”
Section: Discussionmentioning
confidence: 99%
“…A companion article, which details the sleep and alertness of a subgroup of interns in this trial, shows that those who followed flexible schedules did not sleep for shorter periods than those in standard programs but did change their sleep patterns to compensate for longer shifts. 2 Either way, this trial suggests that well-meaning regulations that were designed to correct past problems in hospitals need to be judged against their current relevance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the trial assessed sleep patterns and alertness among interns, with findings that showed noninferiority of the duration of sleep in the flexible programs to that in the standard programs (see the article by Basner et al in this issue of the Journal ). 2…”
mentioning
confidence: 99%